2006
DOI: 10.1074/jbc.m506635200
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Protein 7B2 Can Be Inactivated by Phosphorylation within the Secretory Pathway

Abstract: The prohormone convertases play important roles in the maturation of neuropeptides and peptide hormone precursors. Prohormone convertase-2 (PC2) is the only convertase that requires the expression of another neuroendocrine protein, 7B2, for expression of enzyme activity. In this study, we determined that 7B2 can be phosphorylated in Rin cells (a rat insulinoma cell line) and cultured chromaffin cells, but not in AtT-20 cells (derived from mouse anterior pituitary). Phosphoamino acid analysis of Rin cell 7B2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…This was achieved using a 2D differential phosphoproteomics approach to analyze the RNC‐soluble proteins enriched fraction. Among the proteins found to be modulated by phosphorylation in this study, some are particularly relevant, namely: (i) calpain, a serine protease that appears to be phosphorylated exclusively in starfish injured RNC, indicating that this PTM might be responsible for the modulation of its proteolytic activity during starfish nerve cord regeneration events, similar to what was previously described in other organisms ; (ii) spectrin, one of calpain's preferred substrate, which was found to be dephosphorylated in starfish injured nerves (48 h and 13 days PAA), thus increasing its vulnerability toward calpain‐mediated degradation , a regenerative event that triggers cell membrane rearrangements toward the formation of the growth cone; (iii) Notch homologue, which was dephosphorylated in injured RNC, thus acting as a possible inductor of cell differentiation during RNC regeneration ; (iv) phosphorylation‐mediated re‐organization of the cytoskeleton and regulation of filaments and microtubules dynamics; (v) phosphorylation of a START domain‐containing protein, known to be involved in important lipid‐signaling events during neuronal regeneration, and finally, (vi) dephosphorylation‐induced activation of a neuroendocrine convertase that might be involved in the maturation of signaling neuropeptides during RNC regeneration events.…”
Section: Introductionsupporting
confidence: 74%
“…This was achieved using a 2D differential phosphoproteomics approach to analyze the RNC‐soluble proteins enriched fraction. Among the proteins found to be modulated by phosphorylation in this study, some are particularly relevant, namely: (i) calpain, a serine protease that appears to be phosphorylated exclusively in starfish injured RNC, indicating that this PTM might be responsible for the modulation of its proteolytic activity during starfish nerve cord regeneration events, similar to what was previously described in other organisms ; (ii) spectrin, one of calpain's preferred substrate, which was found to be dephosphorylated in starfish injured nerves (48 h and 13 days PAA), thus increasing its vulnerability toward calpain‐mediated degradation , a regenerative event that triggers cell membrane rearrangements toward the formation of the growth cone; (iii) Notch homologue, which was dephosphorylated in injured RNC, thus acting as a possible inductor of cell differentiation during RNC regeneration ; (iv) phosphorylation‐mediated re‐organization of the cytoskeleton and regulation of filaments and microtubules dynamics; (v) phosphorylation of a START domain‐containing protein, known to be involved in important lipid‐signaling events during neuronal regeneration, and finally, (vi) dephosphorylation‐induced activation of a neuroendocrine convertase that might be involved in the maturation of signaling neuropeptides during RNC regeneration events.…”
Section: Introductionsupporting
confidence: 74%
“…Thus, 7B2 appears to have novel anti-aggregation domains. The role of the known post-translational modifications of this protein, sulfation (49) and phosphorylation (50, 51) (see Fig. 4 A ), in anti-aggregation remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…In membrane fractions from mammalian cells, ER-and Golgi apparatus-associated casein kinase-like activities have been identified that are believed to be involved in the biogenesis of secretory phosphoproteins including proteins involved in biomineralization of bone and teeth (e.g. osteopontin, bone sialoprotein, and dentin sialophosphoprotein) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, to date the primary structures of these kinases have remained elusive.…”
mentioning
confidence: 99%